The Characteristic of Gelatin from Bones of Local Chicken (Gallus gallus domesticus), Broiler Chicken (Gallus domesticus) and Duck (Anas plathytynchos) - Pratikto, Monica Natasha; Rosida , Dedin Finatsiyatull (Nusantara Science and Technology Proceedings, 2023)
Gelatin is a protein derivative that can be extracted from bone. Poultry bones are a by-product of public consumption. So far, poultry bones have not been used optimally and one of the alternatives that can be used for the manufacture of gelatin. The purpose of this study was to determine the characteristics of the bone gelatin of local chicken, broiler and duck produced. The experimental design used was a completely randomized design with a factorial pattern with two factors. The first factor was the type of bone is local chicken, broiler and duck. The second factor was the hydrolysis temperature is 55ºC, 65ºC, and 75ºC. The data were analyzed using ANOVA with a 95% confidence interval. If there was real different then proceed with the Duncan Test (DMRT) of 5%. The optimum treatment was obtained from broiler chicken bones at 75ºC temperatures hydrolysis with yield 11.02%, moisture 8.18%, ash 0.83%, protein 67.48%, gel strength 252.07 g bloom, viscosity 5.95 cP, fat 6.45%, gel point 17.3ºC, melting point 60.35ºC. The organoleptic analysis skoring was scent (4,16), color (4,76), texture (3,48). Fourier transform infrared (FTIR) spectra of gelatin broiler chicken 75ºC temperatures hydrolisis the presence of band corresponding to O-H, N-H, CH2, C=C, C=O, C-N, C-H alkena and aromatic ring, C-O carboxylate acid.